2021
DOI: 10.1029/2020jc016973
|View full text |Cite
|
Sign up to set email alerts
|

Regional Trends in Southern Ocean Eddy Kinetic Energy

Abstract: The Southern Ocean is also characterized by high levels of eddy activity associated with instabilities of the ACC. These eddies play essential roles in the Southern Ocean dynamics and thermodynamics. For instance, mesoscale eddies vertically transfer momentum from the sea surface to the bottom of the ocean (Rin-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 49 publications
7
21
0
Order By: Relevance
“…The 50‐member ensemble of eddy‐permitting ocean‐sea ice model simulations investigated here demonstrate that inference about the EKE response of a single ensemble member to variable forcing in a localized region is not robust, broadly consistent with the findings of Zhang et al. (2021). This point is clarified in Figure 6 which shows a map of the intrinsic fraction of interannual variance, R i , from eddy statistics interpolated onto a coarse (4° × 4°) grid, with eddy contributions filtered using a 12‐month rolling mean.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The 50‐member ensemble of eddy‐permitting ocean‐sea ice model simulations investigated here demonstrate that inference about the EKE response of a single ensemble member to variable forcing in a localized region is not robust, broadly consistent with the findings of Zhang et al. (2021). This point is clarified in Figure 6 which shows a map of the intrinsic fraction of interannual variance, R i , from eddy statistics interpolated onto a coarse (4° × 4°) grid, with eddy contributions filtered using a 12‐month rolling mean.…”
Section: Discussionsupporting
confidence: 83%
“…On longer timescales, it has also been proposed that EKE has increased over recent decades (Hogg et al, 2015;Martínez-Moreno et al, 2019. The robustness of this wind-EKE relationship in the Southern Ocean was recently investigated by Zhang et al (2021), who used crossover data from satellite observations (as in Hogg et al, 2015) to better estimate the EKE on regional scales. By fine-graining these calculations it was found that only a single region (30°-wide in longitude) expressed a significant long-term trend in EKE.…”
mentioning
confidence: 99%
“…The simulations shown here advocate for a probabilistic approach to understanding the Southern Ocean eddy field. The 50-member ensemble of eddy-permitting ocean-sea ice model simulations investigated here demonstrate that inference about the EKE response of a single ensemble member to variable forcing in a localized region is not robust, broadly consistent with the findings of Zhang et al (2021). This point is clarified in Figure 6 which shows a map of the intrinsic fraction of interannual variance, R i , from eddy statistics interpolated onto a coarse (4° × 4°) grid, with eddy contributions filtered using a 12-month rolling mean.…”
Section: Discussionsupporting
confidence: 68%
“…For instance, Zhang et al. (2021) illustrate that the standing meander associated with the Campbell Plateau governs trends in EKE over the full Pacific basin. This may also extend to air‒sea flux properties; for example, Langlais et al.…”
Section: Discussionmentioning
confidence: 99%
“…Localized processes may shape the temporal evolution of air-sea fluxes across the Southern Ocean. For instance, Zhang et al (2021) illustrate that the standing meander associated with the Campbell Plateau governs trends in EKE over the full Pacific basin. This may also extend to air-sea flux properties; for example, Langlais et al (2017) show that standing meanders dominate the transfer of anthropogenic carbon to AAIW.…”
Section: Discussionmentioning
confidence: 99%